2004
DOI: 10.1038/sj.gene.6364056
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of disease susceptibility, inflammation and cytokine profile in lmr1/2 congenic mice infected with Leishmania major

Abstract: Severity of disease caused by Leishmania major depends on the genetics of the host. Early induction of T helper cell type 1 (Th1)-type responses in resistant C57BL/6 mice and T helper cell type 2 (Th2) in susceptible BALB/c mice is thought to determine cure or disease respectively. We have mapped three loci that confer susceptibility or resistance upon congenic mice on the C57BL/6 or BALB/c backgrounds. Here we examine the histopathology and production of interleukin 4 (IL-4) and interferon gamma (IFN-g) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…Mice congenic for all three resistant lmr alleles [strain C.B6-(lmr1, lmr2)] were generated on the susceptible Bc background and were shown to be more resistant to L. major and more able to heal noninfectious wounds than Bc mice, exhibiting a statistically significant tendency toward the phenotype of the donor strain B6. Furthermore, resistance to L. major was independent of T helper cell responses (12,13,30). The conclusions from these studies were that lmr1, -2, and -3 control the rate of wound healing and L. major host response independently of T helper cell responses and that a vigorous wound healing response was required for lesion resolution during L. major infection.…”
mentioning
confidence: 61%
“…Mice congenic for all three resistant lmr alleles [strain C.B6-(lmr1, lmr2)] were generated on the susceptible Bc background and were shown to be more resistant to L. major and more able to heal noninfectious wounds than Bc mice, exhibiting a statistically significant tendency toward the phenotype of the donor strain B6. Furthermore, resistance to L. major was independent of T helper cell responses (12,13,30). The conclusions from these studies were that lmr1, -2, and -3 control the rate of wound healing and L. major host response independently of T helper cell responses and that a vigorous wound healing response was required for lesion resolution during L. major infection.…”
mentioning
confidence: 61%
“…In a study investigating L. major infections in Balb/c mice, high levels of IL-4 in the draining lymph nodes correlated with the lesion size, thus indicating the disease severity. 10 Other authors have associated a TH2 response with high production of IL-4 to an enhanced susceptibility of some strains of mice to Leishmania amazonensis. 2 In contrast, Kropf et al have shown that IL-4-deficient BALB/c mice infected with L. major developed progressive lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The virulent cloned line V121, derived from the L. major isolate LRC-L137 (MHOM͞IL͞67͞ JerichoII), was used to infect bone marrow-derived macrophages at a ratio of five parasites per cell, as described (21). Mice were infected with L. major as described (19,20).…”
Section: Methodsmentioning
confidence: 99%
“…These mice differ in susceptibility from their parental lines, exhibiting a statistically significant tendency toward the phenotype of the donor, away from that of the recipient strain (19). Mice congenic for resistance loci lmr1-3 show no role for T cell modulation of the susceptibility phenotype (19,20), suggesting that T cell responses may act elsewhere in the process (9).…”
mentioning
confidence: 99%